Go Green Campaign Strategy By Pandawara Group Throug Instagram @Pandawaragroup - Nara Anisa Putri (Jogjakarta Communication Conference (JCC), 2024)
This study aims to determine the strategy of the go green movement campaign carried out by Pandawara Group through Instagram media in its account named @PandawaraGroup which currently has 2.4 million followers. The Pandawara group community itself has succeeded in providing positive energy through its campaign on social media for the community to care more about the environment, especially for today's young people. In this study, the authors used qualitative methods Qualitative description with a narrative descriptive approach used to analyze Pandawara's social action strategy in instilling environmental concern to his followers on Instagram media, while the data in this study will use observational data and literature studies, this study will illustrate how youth efforts in campaigning about caring for the environment have enormous benefits for life that lasts. The results of this study show that youth social actions not only involve physical waste reduction activities, but also involve educational aspects through programs carried out by Pandawara Group in campaigning on Instagram media. Utilization of the Instagram platform as a tool to invite the community. In this situation, Pandawara Group invites, introduces, embraces all community groups to join together and voluntarily carry out social actions to care, cleanse, and Care for the environment in order to overcome an urgent problem, namely garbage cleaning.